Optimization of Rhizopus Sp. Growth Media for Biofoam Manufacture: Effect of Temperature and Substrate Composition (Jurnal Bahan Alam Terbarukan, 2022)
Biofoam is a biodegradable material that can substitute the use of styrofoam. Biofoam can be produced from Rhizopus sp. mycelia. In the development of biofoam from fungal mycelia, mycelia act as a reinforcement or binder for the substrate (media) because mycelia grow and spread throughout the substrate. Therefore, optimization of the growth medium of Rhizopus sp. by varying the substrate composition and incubation temperature had been done in this research. The substrate consisted of sugarcane trash (particle size 20, 40, and 60 mesh), starch (soybean, sago, and rice), CaCO3, and distilled water. Rhizopus sp. inoculum that had been mixed with the substrate was incubated at certain temperatures (29 and 35°C) for 7 days. The FESEM-EDS analysis of starches showed that soybean has more nutrients than rice and sago starch. The optimum substrate for the mycelia growth of the Rhizopus sp. is TK 1, which consists of 20 mesh sugarcane trash, soybean flour, CaCO3, and distilled water with an incubation temperature of 29°C. That mycelia grew well and evenly distributed throughout the TK 1 substrate with an average length of ± 1.3 cm. The mycelia distribution throughout the media can also be seen by morphology analysis using Kayence digital microscope.The suitable substrate composition and incubation temperature can optimize the growth of Rhizopus sp. mycelia.